Chaos, control, and synchronization in some fractional-order difference equations - Khennaoui, Amina-Aicha; Ouannas, Adel; Bendoukha, Samir; Grassi, Giuseppe; Wang, Xiong; Pham, Viet-Thanh; Alsaadi, Fawaz E. (Advances in difference equations, 2019)
In this paper, we propose three fractional chaotic maps based on the well known 3D Stefanski, Rössler, and Wang maps. The dynamics of the proposed fractional maps are investigated experimentally by means of phase portraits, bifurcation diagrams, and Lyapunov exponents. In addition, three control laws are introduced for these fractional maps and the convergence of the controlled states towards zero is guaranteed by means of the stability theory of linear fractional discrete systems. Furthermore, a combined synchronization scheme is introduced whereby the fractional Rössler map is considered as a drive system with the response system being a combination of the remaining two maps. Numerical results are presented throughout the paper to illustrate the findings.